Phenotypic and Molecular Identification of Trichophyton Rubrum and Microsporum gypseum of Dermatophytosis - Jawad K. Abood Al-Janabi (Journal of Global Pharma Technology, 2017)
Introduction: Dermatophytes fungi are the predominant source of skin, hair, and nails infection. The present study was carried out to identify and characterize the species of dermatophytes. Material and Methods: Predicated upon the convectional methods such as morphological and microscopic features, culture and biochemical techniques along with growth comparison on Sabouraud dextrose agar (SDA). Two species of fungi belonging to genera Trichophyton and Microsporum were culled to pursue ITS predicated PCR amplification of their genetic profile. Results: The results of PCR amplification have shown that the ITS region, including 5.8S was successfully amplified by utilizing ITS1 and ITS4 as a primers. The amplicon size of dermatophytes species appeared in between 680-720bp, four isolates of T. rubrum and one isolate of M. gypseum were recorded in various regions of the patients bodies. Other fungi (non dermatophytes) such as Geotrichium candidaus, Candida albicans, Pencillium nutatum, Alternaria alternata, Aspergilus niger and Fusarium sp. were also observed on the infected human body with amplicon size in the range of 350-590 bp. Conclusion: These results have suggested not only a valuable baseline to identify pathogenic fungi but additionally emphasizes on future efforts toward the obviation of dermatophytic infections in our region.Keywords: Identification, Trichophyton, Macrosporu m, Dermatophyte mycosis.